Advertisements
Advertisements
Question
The dual of (X' + 1) · (Y' + 0) = Y' is ______.
Options
X · 0 + Y · 1 = Y
X' · 1 + Y' · 0 = Y
X' · 0 + Y' · 1 = Y
(X' + 0) + (Y' + 1) = Y'
Solution
The dual of (X' + 1) · (Y' + 0) = Y' is X' · 0 + Y' · 1 = Y.
Explanation:
According to the duality principle, all 1's are changed to 0 and 0's to 1's. All '+' are changed to '·' and all '·' are changed to '+'.
Here is the expression: (X' + 1) · (Y' + 0) = Y'
Dual is : (X' · 0) + (Y' · 1) = Y'
APPEARS IN
RELATED QUESTIONS
The reduced expression of the Boolean function F(P, Q) = P' · + P · Q is ______.
With reference to the code given below, answer the questions that follow along with dry run/working.boolean num(int x)
{ int a=1}
for (int c=x; c>0; c/<10}
a*=10;
return (x*x%a)=x;
}
- What will the function num() return when the value of x = 25?
- What is the method num() performing?
According to the Principle of duality, the Boolean equation
(A+ B') • (A+ 1) =A+ B' will be equivalent to ______.
Verify if the following proposition is a Tautology, Contradiction or Contingency using a truth table.
((A=>B)∧(B=>C))=>(A=>C)
Find the complement of the following expression and reduce it by using Boolean laws.
P•( 13 ± Q)•Q•(Q+R')
How is a decoder different from a multiplexer?
According to the Principle of duality, the Boolean equation (Aꞌ + B) • (1 + B) = Aꞌ + B will be equivalent to ______.
Distributive law states that ______.